Acute Effects of Different Plyometric and Strength Exercises on Balance Performance in Youth Weightlifters - Werfelli, Hanen; Hammami, Raouf; Selmi, Mohamed Amine; Selmi, Walid; Gabrilo, Goran; Clark, Cain C. T.; Duncan, Michael; Sekulic, Damir; Granacher, Urs; Rebai, Haithem (Frontiers in Physiology, 2021)
Background: High-intensity muscle actions have the potential to temporarily improve performance which has been denoted as postactivation performance enhancement. Objectives: This study determined the acute effects of different stretch-shortening (fast vs low) and strength (dynamic vs isometric) exercises executed during one training session on subsequent balance performance in youth weightlifters. Materials and Methods: Sixteen male and female young weightlifters, aged 11.3 ± 0.6 years, performed four strength exercise conditions in randomized order including dynamic strength (DYN)- (3-sets of 3-repetitions of 10 RM) and isometric strength exercises (ISOM)- (3-sets of maintaining 3-seconds of 10 RM of back-squat), as well as fast (FSSC)- (3-sets of 3-repetitions of 20-cm drop-jumps), and slow (SSSC) (3-sets of 3 hurdle-jumps over a 20-cm obstacle) stretch-shortening cycle protocols. Balance performance was tested before an after each of the four exercise conditions in bipedal stance on an unstable surface (i.e., BOSU ball with flat side facing up) using two dependent variables, i.e., center of pressure surface area (CoP SA) and velocity (CoP V). Results: There was a significant effect of time on CoP SA and CoP V (F(1,60) = 54.37, d=1.88, p<0.0001; F(1,60) = 9.07, d=0.77, p=0.003). In addition, a statistically significant effect of condition on CoP SA and CoP V (F(3,60) = 11.81, d=1.53, p<0.0001; F(3,60) = 7.36, d=1.21, p=0.0003) was observed. Statistically significant condition-by-time interactions were found for the balance parameters CoP SA (p<0.003, d = 0.54) and CoP V (p<0.002, d=0.70). Specific to contrast analysis, all specified hypotheses were tested and demonstrated that FSSC yielded significantly greater improvements than all other conditions in CoP SA and CoP V (p<0.0001 [d=1.55]; p=0.0004 [d=1.19], respectively). In addition, FSSC yielded significantly greater improvements compared with the two conditions for both balance parameters (p<0.0001 [d=2.03]); p<0.0001 [d=1.45]). Conclusions: Fast stretch shortening cycle exercises appear to be more effective to improve short-term balance performance in young weightlifters. Due to the importance of balance for overall competitive achievement in weightlifting, it is recommended that young weightlifters implement dynamic plyometric exercises in the fast-stretch-shortening cycle during the warm-up to improve their balance performance.